Influence of Biodiesel Waste Cooking Oil on Produce Hydrocarbon Fraction by Catalytic Cracking Waste Polystyrene and its Application in Gasoline Engine - Juwono, Hendro; Elliyanti, Ardita; Pamungkas, Firman Satria; Assari, Anas; Dermawan, Ahmad Hawky; Nurfitriyah, Arifah (ALCHEMY, 2019)
Liquid fuel from polystyrene waste and waste cooking oil biodiesel was successfully obtained through catalytic cracking using Al-MCM-41/Ceramic. The structure, morphology, acidity, and porosity of the catalyst were studied by SEM-EDX, pyridine FTIR, and N2 gas adsorption-desorption. The products of catalytic cracking were analyzed using gas chromatogram-mass spectroscopy (GC-MS). The highest yield was obtained at feedstock variations of 57% (P): 43% (M) with the number of hydrocarbon fractions ( C7) is 0.48%, hydrocarbon fraction (C8 - C12) is 20.99%, and hydrocarbon fraction ( C12) is 78.53% in the cracking time 1 hours. Physical characteristics were reported in the form of density, flash point, and caloric value respective. The performance of liquid fuels with commercial fuels, Premium (RON 88), and additives of methyl tertiary butyl ether (MTBE) comparisons of 225 (mL): 750 (mL): 18.25 (mL) respectively produce thermal efficiency on engine use gasoline generator sets was 28.22% at the load of 2118 Watts. Based on this research, all variations of feedstock produce liquid fuels that are in accordance with SNI 06-3506-1994 concerning the quality of gasoline fuel types.Â Keywords: Catalytic cracking, polystyrene waste, waste cooking oil, liquid fuel